The Effect of Knowledge Management on the Competitive Advantage A Field Study on a Sample of Algerian Institutions - داودي , عبد الهادي (Finance and Business Economies Review, 2021)
This study aims to measure the impact of knowledge management on the competitive advantage in some Algerian institutions in order to know the role that knowledge management play in improving the competitive advantage. For this purpose a questionnaire was prepared of 32 units, 30 of which were retrieved suitable for analysis. The questionnaire included 77 questions, 38 of them related to knowledge management and the rest related to competitive advantage. It was found that knowledge management is significantly affected the competitive advantage which calls for the institutions studied to give more attention to knowledge management.